THE DESIGN OF OBJECT-ORIENTED KNOWLEDGE MANAGEMENT SYSTEM FOR TEACHERS IN ISLAMIC BOARDING SCHOOL OF ROUDLATUL QURAN METRO CITY - Sulistiyanto -; Sri Karnila (Prosiding International conference on Information Technology and Business (ICITB), 2015)
Knowledge is contextual, relevant and actionableinformation. Knowledge is different from data andinformation, because it is inside a person s mind. To makeknowledge become intangible asset that can be managedand used by many people requires a knowledgemanagement.Islamic Boarding School of Roudlatul Quran Metro city isa educational foundation with resourceful teaching staffs,but they are not well-organized, so their teaching skill isconsidered static because they are not accustomed tohaving a share of teaching knowledge and materials withothers. With the implementation of knowledgemanagement, it is expected that the teachers teaching andsubject knowledge will become intangible assets that canused optimally.The development of Knowledge Management System(KMS) uses Knowledge Management Roadmap (KMR).Knowledge Management Roadmap helps the developmentof KMS development implementation, from makingBusiness-Driven knowledge, analysis and design, systemdevelopment and implementation. The systemdevelopment method done in the making of KMS usesObject Oriented System. The result of the research is aportal of web-based Knowledge Management System usedas media to document and share subject knowledgeextensively.KEY WORDS: Knowledge Management System (KMS)Knowledge Management Roadmap (KMR), ObjectOriented